Дистанційна радіаційна динамічна теплометрія у контролі перебігу гнійно-некротичних ускладнень синдрому діабетичної стопи - Міщенко, В. В.; Горячий, В. В.; Строганов, П. В.; Сінгіт, Бхалла (Clinical Endocrinology and Endocrine Surgery, 2009)
110 patients with diabetes and the purative-inflammatory diseases of soft tissues were threated. In a complex treatment the preparation of "Dioksizol'" was utilized during 9,3±0,6 days. The disarticulation of fingers of foot with the resection of heads of metatarsus bones were executed in 12 patients, in 6 patients amputations of extremity was made, in 92 patients the volume of operative interventions consisted in opening of phlegmons and necretomy. The initial level of thermal balance as a closeness of thermal stream from a wound was 546±14 u.t. at a base-line level to the 198±9 u.t. At comparing to initial thermal balance in the first 2-4 days acute growth of thermal stream (28,7%,40,2%) was marked with a subsequent its decline on 6,8,10 days (16,7%,-1,5%.-3,5%) of .These descriptions of level of thermal balance are objective information of the state of microcirculation, metabolism and degenerative-regenerative processes, which are taken place in a wound.